2017
DOI: 10.1016/j.foodchem.2017.03.130
|View full text |Cite
|
Sign up to set email alerts
|

Human intervention study to investigate the intestinal accessibility and bioavailability of anthocyanins from bilberries

Abstract: We investigated the importance of the large intestine on the bioavailability of anthocyanins from bilberries in humans with/without a colon. Low bioavailability of anthocyanins in plasma and urine was observed in the frame of this study. Anthocyanins reached the circulation mainly as glucuronides. Analysis of ileal effluents (at end of small intestine) demonstrated that 30% of ingested anthocyanins were stable during 8h passage through the upper intestine. Only 20% degradants were formed and mostly intact anth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
106
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 111 publications
(121 citation statements)
references
References 45 publications
7
106
0
2
Order By: Relevance
“…In these animal studies, the anti‐inflammatory effects were tentatively attributed to the presence of blueberry polyphenols such as anthocyanins and/or proanthocyanidins . However, recent human studies have consistently shown that blueberry polyphenols, including anthocyanins, flavan‐3‐ols, proanthocyanidins and flavonols, have limited bioavailability . In contrast, their metabolites, mainly the phenolic acids, can be detected in plasma at higher concentrations relative to the parent polyphenols.…”
Section: Introductionmentioning
confidence: 99%
“…In these animal studies, the anti‐inflammatory effects were tentatively attributed to the presence of blueberry polyphenols such as anthocyanins and/or proanthocyanidins . However, recent human studies have consistently shown that blueberry polyphenols, including anthocyanins, flavan‐3‐ols, proanthocyanidins and flavonols, have limited bioavailability . In contrast, their metabolites, mainly the phenolic acids, can be detected in plasma at higher concentrations relative to the parent polyphenols.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, anthocyanins have a great potential in various fields, such as the pharmaceutical and food industries. However, the relatively low stability and bioavailability of anthocyanins are the primary barrier to limit the wide and effective applications [9][10][11], raising up the importance of reducing the degradation of anthocyanins and controlling release. So far, encapsulation [12][13][14][15], composite [16][17][18][19] and group substitution [20][21][22][23][24] are the three main means used for anthocyanin stabilization.…”
Section: Introductionmentioning
confidence: 99%
“…The unequivocal identity of the metabolites of C3G was recently established from an elegant human feeding study that used penta-13 C-labelled C3G that allowed the source of the metabolites (A-or B-ring of the anthocyanidin) to be established [37,38]. In addition, a number of metabolites of D3G and other trihydroxylated-and methylated-B ring anthocyanins have been reported, although anthocyanin-rich dietary sources were used instead of pure or isotope-labelled compounds [54]. The quantity of the parent (un-metabolized) 13 C-C3G was very low (about 0.147 µm of 13 C-labelled C3G), while the concentration of phenolic metabolites ranged from 0.1 to 2 µM with the cumulative concentration of metabolites reaching 10 µM [38,55] In summary, the data presented in this study do not support the notion that anthocyanins and/or their metabolites significantly affect PON1 gene promoter activity or change the activity of PON1 enzymes.…”
Section: Discussionmentioning
confidence: 99%